Penerapan Rekayasa Nilai Pada Produk Spring Bed Tipe Romano - Fery Yulianto (Jurnal Teknik Industri, 2003)
"UD.  Dominico", Pasuruan forms the enterprise of furniture sector.  But, the condition of design and facility of spring bed, type of romano cannot give satisfaction enough to the customer, especially the design and facility.  In  this case, there are some complaints  from the customer,  so volume of spring bed sale decreased. The problem took how to make a planning of design and facility of spring bed, especially type of"Romano".The application of Value Engineering  is the way to solve a problem above with terms that have determined or recomanded.